IMPROVING METHODOLOGICAL STRATEGIES FOR SATELLITE CELLS COUNTING IN HUMAN MUSCLE DURING AGEING - Sajko, Špela; Kubínová, Lucie; Kreft, Marko; Dahmane, Raja; Wernig, Anton; Eržen, Ida (Image Analysis and Stereology, 2011)
Stereological methods, based on the optical disector principle and fluorescent staining, were developed for estimating frequency of satellite cells in skeletal muscles. The parameter NL(sc, fib) (number of satellite cells per fibre length) was compared with the parameter NN(sc, nucl) (the percentage of satellite cell nuclei in all muscle nuclei), most often published in the literature, by applying unbiased sampling and counting procedures and using a confocal microscope. The methods were tested in autopsy samples of four young vs. four old human vastus lateralis muscles. Both parameters NL(sc, fib) and NN(sc, nucl) declined during ageing. However, it appears that the two parameters cannot be substituted one by the other because the number of nuclei per fibre length tends to be increased during aging. Using the introduced methods, it is more straightforward to estimate NL(sc, fib) than NN(sc, nucl).